A reduced-order model-based study on the effect of intermittent pneumatic compression of limbs on the cardiovascular system. (April 2016) - Maffiodo, Daniela; De Nisco, Giuseppe; Gallo, Diego; Audenino, Alberto; Morbiducci, Umberto; Ferraresi, Carlo
This work investigates the effect that the application of intermittent pneumatic compression to lower limbs has on the cardiovascular system. Intermittent pneumatic compression can be applied to subjects with reduced or null mobility and can be useful for therapeutic purposes in sports recovery, deep vein thrombosis prevention and lymphedema drainage. However, intermittent pneumatic compression performance and the effectiveness are often difficult to predict. This study presents a reduced-order numerical model of the interaction between the cardiovascular system and the intermittent pneumatic compression device. The effect that different intermittent pneumatic compression operating conditions have on the overall circulation is investigated. Our findings confirm (1) that an overall positive effect on hemodynamics can be obtained by properly applying the intermittent pneumatic compression device and (2) that using intermittent pneumatic compression for cardiocirculatory recovery is feasible in subjects affected by lower limb disease.